PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT GENERASI PASTI SUKSES JAKARTA BARAT - Haris Maulana Putra; Dodi Prasada (Journal of Research and Publication Innovation, 2025)
This study aims to determine how the influence between work motivation and work environment on employee performance at PT Generasi Pasti Sukses West Jakarta, both partially and simultaneously. The method used in this research is quantitative method. Sampling in this study using saturated samples obtained as many as 50 respondents. The results of this study indicate that the work motivation variable partially has a positive and significant effect on employee performance which is characterized by the value of t count (5.209) > t table (2.011) with a significance value of 0.000 <0.05. Then the work environment variable partially has a positive and significant effect on employee performance. Then the work environment variable partially has a positive and significant effect on employee performance. Then the work environment variable partially has a positive and significant effect on employee performance. Then the work environment variable partially has a positive and significant effect on employee performance as indicated by the t value (5,623) > t table (2,011) with a significance value of 0.000 <0.05. Based on the F (simultaneous) hypothesis test, it can be seen that the calculated F value is 17.737> F table 3.195 with anova output significance value of 0.000 <0.05, this means that the work motivation and work environment variables have a positive and significant effect on employee performance at PT Generasi Pasti Sukses West Jakarta.